Fauna de flebotomíneos, taxa de infecção natural e hábito alimentar de Lutzomyia cruzi em Jaciara, Mato Grosso - Brito, Veruska Nogueira de (2013)
Visceral leishmaniasis in Brazil is a disease caused by protozoa of the Leishmania (L.) infantum chagasi, transmitted by Lutzomyia longipalpis and Lu. cruzi. The study of the phlebotomine fauna, along with the research of eating habit and the determination of natural infection rates of these insects by Leishmania is an important tool for the understanding of the epidemiological chain of the leishmanioses and the vectorial competence. The collections of these insects were carried out in the urban area of Jaciara/MT using light traps from 2010 to 2013. The Lutzomyia cruzi females were grouped in pools of up to ten individuals and submitted to PCR in order to determine the rates of natural infection; the engorged females were put in micro tubes individually, for the verification of the host sucked using ELISA. At the end of the 21 campaigns, 2,012 phlebotomines distributed into 24 species with 68.7% of individuals represented by L. cruzi, were captured which together with Lu. whitmani, Lu. sordellii and Brumptomyia brumpti were the most abundant and constant species. Moderate correlation was verified between the number of Lu. cruzi and the temperature. Fourteen pools were positive for L. infantum chagasi with minimum infection rate of 6.1%. By means of ELISA’s test 22 females were reagents for birds anti-serum (28%), dogs (3.3%) and skunks (1.6%), 39 did not react. The results of this study enable us to conclude that Lu. cruzi and Lu. whitmani presents behavior urbanized in the municipality of Jaciara and Lu. cruzi is probably the vector of VL in the city in question, with maintaining the environment facilitated by the presence of chickens and synanthropic animals